Effectiveness of the Potential-Based Capacity Building and Empowerment Program for Santri Students in Ciherang Village: Efektifitas Program Peningkatan Kapasitas Dan Pemberdayaan Santri Berbasis Potensi Di Desa Ciherang - Sopandi, Sopandi; Aminullah Mansur, Angga (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Public perception stigmatizing that Islamic boarding education (pondok pesantren)—especially those which are traditionally conducted (salaf), cannot go after any recent changes and developments and that are very much left behind, has been going on for long. This stereotyping has also been persistently atributed to Tsamrotul Inayah Islamic Boarding School as one of the salaf boarding schools in Kuningan Regency. By applying a descriptive-qualitative approach, this writing aims at describing (1) the possible potentials Tsamrotul Inayah has for its students’ capacitiy building and empowrment (2) the actualization of its students’ capacity building and empowerment, and lastly (3) the effectifity of the students’ capacity building and empowerment. From the perceptional studies conducted, it is concluded that 85, 04% of the trainees gave sophisticating responds—assured that all the four programs conducted are inevitable and beneficial (91,42%), and felt that the programs are worth cotinuing (79, 42%). These findings emphasize that the programs are effective and successful. Through this students’ capacity building and empowerment, it is hoped that the students’ will respectfully get some new competencies and upgraded-skills required to face the future as much as to aleviate the undesirable perception stigmatized on them.